Serum vascular endothelial growth factor receptor-2 and adropin levels in age-related macular degeneration - Ornek, Nurgul; Ornek, Kemal; Aydin, Suleyman; Yilmaz, Musa; Olmez, Yasar (Ijo Press, 2016)
AIM: To investigate the serum levels of vascular endothelial growth factor receptor-2 (VEGFR-2) and adropin in age-related macular degeneration (AMD) patients. METHODS: Ninety-eight AMD patients were included in the study. Seventy-eight age - and sex-matched healthy volunteers were recruited as the control group. Fundus florescein angiography and optical coherence tomography were performed to assess the posterior segment details. Serum VEGFR-2 and adropin levels were measured using enzyme-linked immunosorbent assays and compared between the study groups. RESULTS: AMD group had significantly increased fovea! retinal thickness, serum LDL and HDL levels and significantly decreased subfoveal choroidal thickness (P = 0.01, 0.047, 0.025 and <0.001, respectively). Serum VEGFR-2 level revealed a significant decrease in AMD patients compared to controls (26.48 +/- 6.44 vs 30.42 +/- 7.92 ng/mL, P<0.001). There was an insignificant increase in serum adropin level in AMD patients (6.17 +/- 1-3.19 vs 5.79 +/- 2.71 ng/mL, P=0.4). Serum level of VEGFR-2 in AMD patients had a significant negative correlation with fovea! retinal thickness (r=-0.226, P=0.025) and a significant positive correlation with subfoveal choroidal thickness (r=0.2, P=0.048). CONCLUSION: The current study demonstrated that the decreased serum VEGFR-2 level may be considered in the development of AMD. Adropin does not seem to play a role in the pathogenesis of AMD.
Keywords: vascular endothelial growth factor receptor-2; adropin; age-related macular degeneration